Epigram Theatre by Martial - Packočinaitė-Biržietienė, Skirmantė (Literatūra, 2015)
The article deals with the poetry of famous Roman epigramist Marcus Valerius Martial (Marcus Valerius Martialis (41–104). In some epistolary prefaces to his books of epigrams (e.g. to I epigram book, as well as to II epigram book) he creates the ambience of the theater and it looks as he is inviting his reader to the epigram theater. These passages provide two potential ways of interpretation. First, Martial himself explains the nature of the epigram comparing it with the mime. Mime is a part of the ancient comic theater and was the most popular kind of performance in the Imperial Rome. Also mimes’ performance was a part of some Roman religious festivals, especially to those sacred to the deities of changing time, fertility, nature revival, such as Saturnalia, Floralia. Our poet tells, that epigram is of the same kind as Floralia mimes and contains the force of verbal licence of this feast. Next possible device is to compare epigrammatic heritage of Martial with the New comedy. The history of this comedy begins in the end of the IVth B. C. century in the Greece, but Roman writers of the IInd century B. C. took the most greatest pieces and adapted them to the Roman life. These comedies were interested in the life of the common people, presenting the different types and characters, showing first of all the vice and making it commic. Martial as well declares being interested in the different taints and is going to satirise them, not somebody personal. He is showing a lot of characters simmilar to the personages of the New comedy, such as niggards, whores, drunkards, charlatans, bad teachers, doctors, cooks etc.